2020
DOI: 10.1039/d0ra03773g
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot-sensitized O-linked heptazine polymer photocatalyst for the metal-free visible light hydrogen generation

Abstract: A polymeric O-linked heptazine polymer (OLHP) decorated with S, N co-doped graphene quantum dots (S,N-GQDs) as a photosensitizer to utilize visible light (λ > 420 nm) for hydrogen generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…A lower PL intensity of Ox@CNB was observed as compared with that of BCN, highlighting the obstruction of charge recombination in Ox@CNB. These results indicated that O doping, the terminal −NH 2 group and the porous hollow tubular structure promote the charge‐transfer process in Ox@CNB, restricting charge recombination [66–68] . Interestingly, a red‐shift of the emission peak was observed between the Ox@CNB and BCN spectra.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…A lower PL intensity of Ox@CNB was observed as compared with that of BCN, highlighting the obstruction of charge recombination in Ox@CNB. These results indicated that O doping, the terminal −NH 2 group and the porous hollow tubular structure promote the charge‐transfer process in Ox@CNB, restricting charge recombination [66–68] . Interestingly, a red‐shift of the emission peak was observed between the Ox@CNB and BCN spectra.…”
Section: Resultsmentioning
confidence: 85%
“…These results indicated that O doping, the terminal À NH 2 group and the porous hollow tubular structure promote the charge-transfer process in Ox@CNB, restricting charge recombination. [66][67][68] Interestingly, a red-shift of the emission peak was observed between the Ox@CNB and BCN spectra. The decreased intensity of the emission peak is attributable to the narrow bandgap of Ox@CNB, which is consistent with the results of UV-vis DRS.…”
Section: Chemcatchemmentioning
confidence: 99%
“…However, it is formed at quite high temperatures (450 to 550 °C), and therefore it is only partially characterized, besides the fact that the authors prove that the polymer consists of heptazine units linked by oxygen bridges. In a very recent article, the same authors described a nanocomposite made of highly porous OLHP, coated by S- and N-doped graphene nanoparticles . They show that due to the composite material, both because of the high porosity and the complementarity of the partners (the gC dots acting as electron reservoirs), the hydrogen evolution is considerably enhanced compared to OLHP, ultimately reaching values of 23.9 mmol g –1 h –1 .…”
Section: Supramolecular Chemistry Of S-heptazines: Liquid Crystals An...mentioning
confidence: 99%
“…In a very recent article, the same authors described a nanocomposite made of highly porous OLHP, coated by S-and N-doped graphene nanoparticles. 132 They show that due to the composite material, both because of the high porosity and the complementarity of the partners (the gC dots acting as electron reservoirs), the hydrogen evolution is considerably enhanced compared to OLHP, ultimately reaching values of 23.9 mmol g −1 h −1 . Another promising approach to insert reactive heptazine rings inside a material is the MOF synthesis.…”
Section: Heptazine-based Cofsmentioning
confidence: 99%
“…Although visible light is harmless, the strategy is still appropriate to cure only superficial lumps. 88 , 89 Various research invitations have revealed that QD-conjugated oligonucleotide sequences (attached through surface COOH groups) are targeted to connect with DNA or mRNA. 90 , 91 Bio conjugated QDs are also considered for the site-specific gene as well as drug delivery in cancer.…”
Section: Various Types Of Nanocarrier-based Drug Delivery Systemsmentioning
confidence: 99%